ByzRev 02.2020.013: Eva Elm – Nicole Hartmann (eds.), Demons in Antiquity. Their Perception and Transformation in Different Literary Genres: (Transformationen der Antike 54). Berlin – Boston: De Gruyter 2020. - Filimon, Florin (The Byzantine Review, 2020)
Eva Elm – Nicole Hartmann (eds.), Demons in Antiquity. Their Perception and Transformation in Different Literary Genres (Transformationen der Antike 54). Berlin -- Boston: De Gruyter 2020. 176 pp. – ISBN: 978-3-11-062672-8 (€ 79,95)